Nutritional Education 'GEMAKIN' for Improving Pregnant Women's Knowledge and Attitudes Towards Stunting Prevention Using Audiovisual Media - Nanang Qosim; Dian Luthfita Prasetya Muninggar; Suwarsono Suwarsono (Poltekkes Kemenkes Mataram, 2024)
Background: Stunting is a growth and development disorder that caused children to have short stature. One of the causes of stunting is poor nutritional intake of pregnant women during pregnancy when the fetus is still in the womb. Several intervention was done to address the incidence of stunting include nutrition education for pregnant women. In the coastal areas of Indonesia, there is an abundance of marine wealth, especially fish that are highly nutritious. However, there is a gap between the potential of marine wealth and the low level of fish consumption in Indonesia. The 'GEMAKIN' nutrition education program aims to raise awareness about the importance of fish consumption during pregnancy as part of the critical first 1,000 days of life. Research Purposes: To determine the impact of 'GEMAKIN' nutrition education using audiovisual media on the knowledge and attitudes of pregnant women regarding stunting prevention. Research Methods: The method used in this study is a Quasi-Experimental design with a one-group pre-test and post-test design. The study subjects were 50 pregnant women. Data collection was done using pre-test and post-test intervention instruments. Data analysis was conducted using the Wilcoxon test. Research Result: The results of the study showed a significant increase in knowledge (p=0.000) and attitude scores (p=0.000) before and after the 'GEMAKIN' nutrition education intervention using audiovisual media on pregnant women regarding stunting prevention. Conclusion: The 'GEMAKIN' nutrition education using audiovisual media on stunting prevention can significantly increase the knowledge and attitudes levels of pregnant women in Bandarharjo, Semarang.